2020
DOI: 10.17784/mtprehabjournal.2020.18.1188
|View full text |Cite
|
Sign up to set email alerts
|

Implications of therapeutic touch and relaxation massage on aging

Abstract: Background: The social, technological and scientific advances mainly linked to the health area were important for increasing the longevity of the world population, which highlights the need for studies and public policies aimed at the prevention and treatment of chronic diseases associated with aging. The search for complementary therapeutic techniques and practices to improve the quality of life of the elderly has increased in order to decrease the complications of the aging process such as chronic pain, fati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Deng et al 34 showed in their study that after TT, could sleep better of obstructive sleep apnea syndrome patients. In addition, other studies revealed that TT positively affected the sleep quality of individuals 17,35,36 …”
Section: Discussionmentioning
confidence: 97%
“…Deng et al 34 showed in their study that after TT, could sleep better of obstructive sleep apnea syndrome patients. In addition, other studies revealed that TT positively affected the sleep quality of individuals 17,35,36 …”
Section: Discussionmentioning
confidence: 97%
“…In comparison, light massage in human infants results in 21%–47% more weight gain (Elmoneim et al, 2021). Massage in the elderly also improves both physical and psychological well-being (Micillo et al, 2020). This likely reflects the importance of nurturing touch for the development and maintenance of several biological systems, particularly those involving hormones (e.g., oxytocin, cortisol), the immune response (e.g., inflammation), and brain chemistry (e.g., dopamine, serotonin, and opiates; Ellingsen et al, 2016; Jablonski, 2021; Jakubiak & Feeney, 2017; Kim et al, 2016).…”
mentioning
confidence: 99%